A Revised Surgical Strategy for the Distal Tibiofibular Interosseous Osteochondroma. (8th May 2020) - Yang, Huarui; Shou, Kangquan; Wei, Shijun; Fang, Zhi; Hu, Qiwen; Wan, Qiong; Yang, Yi; Bao, Tongzhu
Abstract : Osteochondroma is one of the most common benign bone tumor; however, the surgical treatment still remains a challenge for those that occur at the distal tibiofibular interosseous location. Previously, the transfibular approach has been successfully described, but the potential damage of the syndesmosis would give rise to the instability of the ankle joint and thus may result in the unfavorable long-term outcome. Here, a revised strategy which can protect the syndesmotic complex is introduced. From 2010 to 2017, eleven patients with the distal tibiofibular interosseous osteochondroma who underwent the revised surgery were collected. The distal fibular osteotomy and posterior tibial osteotomy were performed to keep the inferior syndesmosis intact for better stability of the ankle joint. Both the anterior tibiofibular ligaments (AITFL) and posterior tibiofibular ligaments (PITFL) have been preserved successfully, and thus, the stability of the ankle joint has been maintained due to our strategy. The VAS and AOFAS scores were utilized to assess the clinical outcome and function. Postoperatively, all the patients were pain-free and were able to wear the appropriate shoes at the last follow-up. Preoperative and postoperative AOFAS scores were 93.63 ± 6.91 and 47.27 ± 5.27 (P < 0.05 ), respectively. Moreover, the average VAS score was 1.73 ± 0.27 (compared with preoperative as 7.45 ± 2.15, P < 0.05 ), demonstrating obvious improvement after the operation. To our best knowledge, this is the first time to perform the resection of the distal tibial interosseous osteochondroma involving the fibula without interrupting the inferior syndesmotic complex especially the AITFL and PITFL. We believe that this strategy may pave a new way for optimized clinical outcome for these patients with distal tibiofibular interosseous osteochondroma. This clinical trial study is registered with number ChiCTR1900024690 .